1986
DOI: 10.1093/nar/14.2.765
|View full text |Cite
|
Sign up to set email alerts
|

Structure and nucleotide sequence of the 5' region of the human and feline c-sis proto-oncogenes

Abstract: Comparative analysis of cosmid clones containing the human and feline c-sis genetic regions revealed the similar structural organization of these areas in the two species. The areas shared seven different genetic regions in and around the c-sis locus and of these was related to v-sis. Another region, 1.9 kbp in size and located about 8 kbp upstream of the v-sis homologous region in the human genome, also hybridized to the main c-sis transcriptional product of 3.5 kb. Comparison with a recently described c-sis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

1987
1987
1996
1996

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 41 publications
0
19
0
Order By: Relevance
“…Another possible cause of inaccessibility of the c-sis promoter for activating transcription factors is methylation of essential CpG dinucleotides. Four CpG dinucleotides are located within the first 100 bp upstream of the c-sis transcriptioninitiation site (van den Ouweland et al, 1986) and their methylation status is currently being examined.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Another possible cause of inaccessibility of the c-sis promoter for activating transcription factors is methylation of essential CpG dinucleotides. Four CpG dinucleotides are located within the first 100 bp upstream of the c-sis transcriptioninitiation site (van den Ouweland et al, 1986) and their methylation status is currently being examined.…”
Section: Discussionmentioning
confidence: 99%
“…A site at + 0.4, which extends from approximate position + 280 to + 500, was found in the c-sis expressing carcinoma-derived cell lines, but is absent from the placenta cell lines and from K562 cells. Although this site could not be linked to a clear function with respect to transcription regulation, it contains a CpG island (van den Ouweland et al, 1986) and may bind trans-acting factors in vivo (Fig. 4).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Using deletion mutagenesis and the cat reporter gene, we identified a minimum region of 42 bp upstream of the TATA box which was required for promoter activity in uninduced cells (Fig. 7).…”
Section: Discussionmentioning
confidence: 99%
“…Sp1 has been shown to contain several independent transcriptional activation domains in addition to the zinc finger region located within the C terminus of the protein (46) We have demonstrated that the ThR segment within the B region of the PDGF B-chain gene is involved in the transcriptional response to thrombin. The conservation of the ThR region of the PDGF B-chain gene across different species (human (52), feline (52), and murine (53)) suggests that the region may serve as a binding site for important cis-acting elements. If this region is in fact a site responsive to a thrombin-induced transcriptional activator, then one might anticipate finding the CCACCC motif within the promoter region of other thrombinresponsive genes.…”
Section: Interaction Of Sp1 and Tinf With The B Region Of The Pdgf B-mentioning
confidence: 99%